Prevalence of Metabolic Syndrome and Its Components in Patients with Type 2 Diabetes Mellitus: A Cross-Sectional Study at a Tertiary Care Teaching Hospital - Timalsina, Santosh; Pandit, Pratima (Journal of Chitwan Medical College, 2019)
Introduction: The metabolic syndrome (MetS) is a cluster of risk factors that is responsible for most of the excess cardiovascular morbidity amongst patients with Type 2 Diabetes Mellitus (T2DM). Presence of MetS in T2DM markedly increases the risk for coronary heart disease, stroke and premature deaths. This study was undertaken to find the prevalence of MetS and its individual components among patients with T2DM visiting Chitwan Medical College and Teaching Hospital, Bharatpur, Nepal. Methods: A laboratory-based descriptive cross sectional study carried out at CMC-TH between January and August, 2017. Data obtained included anthropometric indices, blood pressure and fasting serum lipid profile. National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III) criteria were used for diagnosis of MetS. Data was analyzed using SPSS version 20. Results: The overall prevalence of MetS among 150 T2DM patients (Mean age= 53.70±10.83 years, Male:Female=84:66) was 60%. The prevalence was higher in females compared to males (75.75% vs.47.62%, P<0.001). High blood pressure was the commonest MetS component. Following that, decreased HDL-c was the predominant component in females whereas raised triglyceride in the males. SBP/DBP, BMI and waist circumference were significantly associated with MetS. Conclusion: The prevalence of MetS is high in diabetic patients, particularly in females and middle age group adults, with high blood pressure and hypertriglyceridemia as the commonest abnormalities. As MetS adds to the cardiovascular risk to the already at-risk diabetic population, timely identification and appropriate intervention is of utmost importance in reduction of disease burden in T2DM patients.